2022
DOI: 10.3390/cancers14153588
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Origin of Cancer Stem Cells in Oral Squamous Cell Carcinoma and Its Clinical Implications

Abstract: Oral squamous cell carcinoma (OSCC) histopathologically accounts for ≥90% of oral cancer. Many clinicopathological risk factors for OSCC have also been proposed, and postoperative therapy is recommended in guidelines based on cancer stage and other risk factors. However, even if the standard treatment is provided according to the guidelines, a few cases rapidly recur or show cervical and distant metastasis. In this review article, we focus on the diversity of the origin of OSCC. We also discuss cancer stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 69 publications
(109 reference statements)
0
19
0
Order By: Relevance
“…CSCs seem to play an important role in the initiation and development of various malignancies [ 29 - 31 ]. The detection of CSCs in solid cancers was firstly confirmed in 2003, by Al-Hajj et al, who showed that only a fraction of CD44+/CD24+ or negative breast cancer cells could create a tumor with the same characteristics of the initial tumor [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSCs seem to play an important role in the initiation and development of various malignancies [ 29 - 31 ]. The detection of CSCs in solid cancers was firstly confirmed in 2003, by Al-Hajj et al, who showed that only a fraction of CD44+/CD24+ or negative breast cancer cells could create a tumor with the same characteristics of the initial tumor [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…They may also be a valuable biomarker to detect HNC patients with resistance to therapy or a high risk of tumor recurrence [ 7 , 72 ]. CSCs have been identified as a small population of cancer cells in tumor tissue in terms of 0.01–2% of total tumor mass that have similar features to embryonic and normal stem cells [ 6 , 73 ]. CSCs have asymmetrical cell division and self-renewal capability, which induce a heterogeneous subpopulation of cancer cells involved in angiogenesis and immortality [ 6 , 7 , 73 ].…”
Section: Cscs In Head and Neck Cancermentioning
confidence: 99%
“…CSCs have been identified as a small population of cancer cells in tumor tissue in terms of 0.01–2% of total tumor mass that have similar features to embryonic and normal stem cells [ 6 , 73 ]. CSCs have asymmetrical cell division and self-renewal capability, which induce a heterogeneous subpopulation of cancer cells involved in angiogenesis and immortality [ 6 , 7 , 73 ]. It is well known that CSCs are more malignant than other subsets of cancer cells in tumor masses.…”
Section: Cscs In Head and Neck Cancermentioning
confidence: 99%
“…CSCs activity is modulated by different signals and cellular interactions provided by the tumor microenvironment, allowing CSCs to achieve highly invasive and aggressive behavior or resist conventional therapies. Thus, activating the Epithelial-to-Mesenchymal Transition (EMT) program by the CSCs represents a valuable strategy to promote invasion, metastasis, and treatment resistance [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…CSCs may originate from adult stem cells or progenitor cells in which the accumulation of mutations over time leads to the activation of transcriptional gene signatures and signaling pathways related to the maintenance of stem cell phenotype and malignant transformation [ 13 - 15 ] . Moreover, differentiated cells can also acquire stemness traits due to genetic instability throughout their division process and dedifferentiate, acquiring stem cell properties [ 16 , 17 ] .…”
Section: Introductionmentioning
confidence: 99%